A new species of Begonia (Begoniaceae) from the eastern mountains of Panama - Lucila Guillén; Peter W. Moonlight; Orlando A. Jara-Muñoz; María Sánchez de Stapf; Juan F. Carrión (PhytoKeys)
Begonia chucantiensis sp. nov. is described as a new species of Begonia section Lepsia from Cerro Chucantí, Darién Province, in eastern Panama. A study of the literature and herbarium specimens, as well as fieldwork, suggests that the new taxon is distinguished from other species in the section by the combination of the following characters: uniform nodes, stipules persistent, 3.3–6 × 0.8–1.7 cm leaf blades, only two flowers per inflorescence, 12–14 stamens, and fruits with wings of similar shape and size. Images, information on geographic distribution, habitat, and a preliminary assessment of the conservation status of the new species are also provided.